Walking, Biking, Driving: Urban Determinants of Active Mobility - Ríos-Llamas, Carlos; Hernández-Vázquez, Samuel (Estoa. Journal of the Faculty of Architecture and Urbanism, 2022)
This paper proposes a review on the urban determinants of active mobility such as car driving, cycling, and walking, based on a compilation of research papers from the period 2019-2020. The applied method consists of a selection of scientific texts in indexed journals. Analysis of thirty papers dealing with the relationship between urban space and active mobility. Data codes and linkages processed with ATLAS.ti to identify the main determinants and web-density. According to the results, among the most important factors to understand active mobility are greenery, sociodemographic determinants, neighborhood design, cycling infrastructure and leisure activities. Finally, we discussed the urban processes of Latin American cities to offer some criteria and promote active mobility.